Exploring Student Teacher Perceptions on the Benefits of the Teaching Practicum - Belén Poveda García-Noblejas; María-Luisa B; Inmaculada Rodríguez-Gómez; Ernesto López-Gómez (Springer, 2023)
Abstract This article examines student teacher perceptions regarding the benefits of the teacher education practicum. For this purpose, a cross-sectional study was performed using a questionnaire. Participants consisted of 455 students from the Early Childhood and Primary Education Degrees studying at a university in the Madrid community. The questionnaire was administered between the academic years of 2017/2018 and 2021/2022 (2019/2020 was excluded due to the pandemic), at the end of each practicum period of the 2nd, 3rd, and 4th year courses of the distinct teaching student cohorts. Results were analyzed based on a quantitative perspective, revealing relevant benefit and utility profiles, confirming that the variable that most modulates student perception is the Practicum period (finding lower scores for the intermediate practicum), followed by the gender variable, and finally, the Degree variable, which has the most stable results. These findings are discussed, highlighting certain proposals to improve teaching practicum programs, and to encourage a better knowledge of the teaching practicum in terms of its benefits and usefulness, considering the teacher candidate perspective.